Comparison of task interspersal ratios on efficiency of learning and problem behavior for children with autism spectrum disorder. Issue 2 (29th November 2018) - Knutson, Sophie C.; Kodak, Tiffany; Costello, Dayna R.; Cliett, Terra
Abstract : The current study extends the literature on task interspersal (TI) by comparing the effects of four different TI ratios on the efficiency of skill acquisition and on levels of problem behavior in children with autism spectrum disorder and related disorders. The four ratios of TI were 3:1, 1:1, 1:3, and 0:1 mastered‐to‐acquisition tasks. An adapted alternating treatments design was implemented to compare the cumulative number of stimuli mastered, mean training time to mastery, rate of acquisition, and the level of problem behavior. The results showed that the 0:1 condition was the most efficient intervention procedure for all four participants. In addition, TI did not lead to a greater reduction in levels of problem behavior.